You're Collating Just Fine and Other Lies You've Been Telling Yourself. Issue 1 (15th December 2021) - Bordalejo, Barbara; Vázquez, Adam
Abstract : Although textual scholars agree that collation is a crucial component of the editing process, it often goes undefined and only briefly explained. This article defines the term, explains different kinds of collation, and explores some of its applications. We emphasize stemmatology and medieval textual traditions. By drawing from editorial examples and the theoretical frameworks of projects centred on works such as the Canterbury Tales, Troilus and Criseyde, Dante's Commedia and the Greek New Testament, the article seeks to compare manual and computer-assisted approaches to collation methods. We delineate the scope of this activity and argue that computer-assisted collation minimizes the risk of missing out on relevant data. We examine the advantages of full-text collation over sample collation and conclude that no decisions about stemmatically significant variation can be made a priory and that variant distribution is the major factor weighing on significance.